If you mean: -3x-5x+1+8x-2x-9 then the result is -2x-8
You try to bring all instances of the variable to one side. Here is an example:5x + 5 = 3x - 2 Subtracting 3x on both sides: 2x + 5 = -2 Subtracting 5 on both sides: 2x = -7
2
Simplifying x2 + -2x + -63 Reorder the terms: -63 + -2x + x2 Factor a trinomial. (-7 + -1x)(9 + -1x) Final result: (-7 + -1x)(9 + -1x)
2X * 2X * 2X = 8X^3 2X^3 is saying 2*( X * X * X) = 2X^3
y = -1/(3x7 + 2x - 9)y = -(3x7 + 2x - 9)-1y' = -(-1)(3x7 + 2x - 9)-2(3x7 + 2x - 9)'y' = (3x7 + 2x - 9)-2(21x6 + 2)y' = (21x6 + 2)/(3x7 + 2x - 9)2
gcf(16x8, 24x7) = 8x7 16x8 = 8x7 x 2x 24x7 = 8x7 x 3
4
2x + 30 = 4x + 22 Subtracting 2x from both sides, 30 = 2x + 22 Subtracting 22 from both sides, 8 = 2x Dividing both sides by 2, 4 = x x = 4
2x + 30 = 4x + 10 Subtracting 2x from each side, 30 = 2x + 10 Subtracting 10 from both sides 20 = 2x Dividing both sides by 2 10 = x x = 10
By subtracting 2x from 3x and getting x, which is equal to 35.
10 by subtracting 2 on both sides
just add the negative of the polynomial, that is the same as subtracting it. For example, x^2+2x is a poly, the negative is -x^2-2x. So if we want to subtract x^2+2x from another poly, we can add the negative instead.
That multiplication and subtraction equation has (2x times 5x) subtracting 84.
-6
The answer is -5x + 2y. The terms with the same variable are combined by adding or subtracting their coefficients, and then the result is written with the corresponding variable. In this case, -3x and -2x combine to give -5x, and 4y and -2y combine to give 2y.
If: 2x+5y = -10 Then by subtracting 2x from both sides: 5y = -2x-10 And dividing all terms by 5: y = -2/5x-2 which is now in slope intercept form